STUDI EFEK PENGGUNAAN BIODIESEL TERHADAP EMISI PADA SEKTOR TRANSPORTASI DI JAKARTA - Soni S Wirawan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Biodiesel has been proven by world wide numerous studies as an environmental friendly alternative diesel fuel. Biodiesel is essentially sulfur free. Engines fueled by biodiesel emit significantly fewer particulates, hydrocarbons and less carbon monoxide than that operating conventional diesel fuel. The maximum utilizationof biodiesel in Indonesia could improve the air quality level in major cities especially in Jakarta. The objective of this study is to assess the effect of biodiesel utilization in transportation sector to the air pollution level in Jakarta. The targeted emission in the study are carbon monoxide (CO), nitrogen oxides (NOx),hydrocarbons (HC), sulfur oxides (SOx) and particulate matter (PM) from vehicle sources. The scenarios used in this study are the utilization of B10 in 2010 and increased to B20 in 2015, B30 in 2020 and B50 in 2025 as an automotive diesel fuel substitution in Jakarta. The result showed that the utilization of biodieselcould improve the air quality level in Jakarta, especially on SO2 and PM emission. By using B10 in 2010, the emission of SO2 and PM will decrease 7,95% (2.070 ton) and 15,62% (1.680 ton) respectively compared to utilizing of pure fossil automotive diesel oil. The highest emission improvement was shown on B50 in2025 scenario. The reduction of SO2 and PM was reached 35,69% (16.660 ton) and 23,21% (4.360 ton) respectively.